Agritech berbasis IOT : Implementasi sistem monitoring dan kontrol proses pembuatan pupuk organik - Alam, Muhammad Wahyu Syafiul; Alemoka, Christian Bill Glain (Jurnal Teknologi Cerdas, 2025)
The problem that often occurs in making organic fertilizers is the incomplete maturity level and inconsistent content results. This is due to many factors ranging from the suitability of temperature and humidity in organic materials, the provision of inappropriate microbial liquids, the pH and TDS content which always changes during the fermentation process. This research aims to develop a system that is able to monitor temperature and humidity, volume of organic material and liquid organic fertilizer, methane gas and carbon dioxide during the fermentation process in real time through a website platform and automatic control of pH and TDS content adjustments in liquid organic fertilizer and notifications on the device within a certain period of time. The results of this study can provide solutions for farmers and Organic Fertilizer producers in the manufacturing process so that it can help reduce the manual process to be automated and the results of Liquid Organic Fertilizer become more consistent.